Long-term surgery outcome for epilepsy and psychogenic nonepileptic seizures in a child with anterior cingulate gyrus dysplasia - Mirandola, Laura (Epilepsy Behav Case Rep, 2015)
We present the case of a 13-year-old child with nocturnal frontal lobe epilepsy (NFLE) related to a right cingulate gyrus cortical dysplasia, who also presented with psychogenic nonepileptic seizures (PNES) and interictal antisocial behavior. The association of drug-resistant epilepsy with behavioral disorders is well established, but the role of epilepsy surgery in these patients is still controversial, especially in children. The key finding is represented by the excellent long-term outcome on both epilepsy and behavioral dysfunction after the surgical excision of the cingulate gyrus cortical dysplasia.